Case Report: Case analysis and literature review of preeclampsia complicated by inevitable abortion progressing to HELLP syndrome with liver rupture and hemorrhage - Xing, Guangyang; Lu, Yani; Sun, Xiaotong (Frontiers in Medicine, 2025)
HELLP syndrome is a severe complication of hypertensive disorders in pregnancy, characterized by hemolysis, elevated liver enzymes, and thrombocytopenia. Severe cases can lead to various complications such as DIC and placental abruption, directly endangering the lives of both the mother and the fetus. Among these, intra-abdominal hemorrhage caused by the rupture of a subcapsular hepatic hematoma is particularly dangerous. Traditionally, the rescue of liver rupture relies on emergency laparotomy. In recent years, the development of interventional radiology has provided a minimally invasive option of transcatheter arterial embolization (TAE) for hemodynamically stable patients. TAE has significant advantages in emergency hemostasis of HELLP-related liver rupture and can reduce maternal and fetal mortality. This case report analyzes a case of preeclampsia complicated with inevitable abortion progressing to HELLP syndrome with liver rupture and hemorrhage. After successful hemostasis with TAE, the patient received comprehensive intensive care including plasma exchange, blood transfusion, and continuous renal replacement therapy. The case emphasizes that early identification, multidisciplinary collaboration, accurate imaging evaluation, TAE for minimally invasive hemostasis, close renal support, and long-term follow-up are the keys to reducing the mortality of HELLP syndrome-related liver rupture and preventing recurrence in future pregnancies.